Applying stakeholder thinking to public relations: An integrated approach to identifying relationships that matter - De Bussy, Nigel (Routledge, 2008)
Despite their obvious parallels, the stakeholder and public relations literatures have developed in relative isolation from one another. This paper draws primarily on stakeholder thinking to address one of the most fundamental issues facing both fields - the question of who exactly should be classified as a stakeholder. A framework based on the notion of stakeholder responsibility is presented as a guide to assist managers assess the legitimacy of potential stakeholders and, consequently, to identify who should be accorded stakeholder status. In the process, some unacknowledged similarities between the public relations and stakeholder literatures are revealed.